IMPLEMENTASI PERATURAN WALIKOTA PEKANBARU NOMOR 7 TAHUN 2011 TENTANG PEDOMAN PEMBERIAN IZIN PENGENDALIAN PEMBUANGAN LIMBAH CAIR (STUDI KASUS LAUNDRY YANG MEMILIKI IZIN USAHA) - Sri Wahyuni; Febri Yuliani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
Laundry is one of the service providers who provide laundry washing facilities that produce liquid waste in the form of detergent liquid. Liquid waste generally contains chemicals and must be processed quickly, then the procedure for implementation has been regulated in the Pekanbaru Mayor Regulation Number 7 of 2011 About Guidelines License for Liquid Waste Disposal Control. The purpose of this study was to find out how the implementation and what factors inhibited Implementation of Pekanbaru Mayor Regulation Number 7 Of 2011 About Guidelines License for Liquid Waste Disposal Control (Case Study Laundry that have Business License). This research uses the concept of policy implementation theory according to Riplay and Franklin in Tahir (2015: 95-96) about the success of policy implementation based on three perspectives, that are: level of bureaucratic compliance, smoothness of the life and no problems and performance. Research uses qualitative case study method by using purposive sampling method as source of information and data collection techniques including observation, interviews, documentation, library techniques and data analysis. The results of this study indicate the Implementation of the Pekanbaru Mayor Regulation Number 7 of 2011 About Guidelines License for Liquid Waste Disposal Control (Case Study Laundry that have Business License) are known to have not been implemented because there are several inhibiting factors namely lack of implementor human resources and lack of awareness of implementors and groups target, so that the Implementation of the Mayor Regulation of Pekanbaru Number 7 of 2011 About Guidelines License for Liquid Waste Disposal Control has not run maximally.Keywords: Implementation, liquid waste, laundry